Optimization of Cellulase Activity by Aspergillus niger and Penicillium chrysogenum using Some Agricultural Wastes - Bukar, A.; Abbas, M. I; Milala, M. A; Isa, M. A; Allamin, I. A; Ismail, H. Y (UMYU Journal of Microbiology Research, 2016)
Cellulases are enzymes used in various manufacturing processes and their production is faced with a number of challenges including high cost of raw materials, low product recovery due to the nature of microbial cells and unfavorable growth conditions leading to high cost of the finished products. This study was therefore designed to investigate the optimum physicochemical conditions that could support the production of large amount of cellulase by Aspergillus niger and Penicillium chrysogenum using agricultural wastes as substrates. Each of the fungal species was grown in a mineral salt media containing either of paper, sugar cane bagasse or wheat bran as sole carbon source at various concentrations. Cellulase activity was observed to be optimum at 5 % w/v using the substrates after 96 hours incubation. The effect of temperature and pH were then assessed and wheat bran was shown to support optimum cellulase activity (5.36 IU and 3.62 IU) at pH 5 and temperature of 30°Cusing both organisms. Using paper however, the optimum enzyme activity (1.28 IU and 1.26 IU) was observed at pH 6 and temperature ranging from 35°C (A. niger) to 45°C (P. chrysogenum). pH 5 was observed to be optimum for cellulase activity using sugar cane bagasse but P. chrysogenum performed better (1.01 IU) at 40°C than A. niger (0.91 IU) at 50°C. Cellulase activity using the two latter substrates was significantly (p< 0.05) lower than that of wheat bran under the said conditions. This study therefore, revealed that the two fungal species are excellent cellulase producers under optimum conditions of 30°C and pH 5 using wheat bran at 5% concentration; hence their potentials for large scale cellulase production.